Ta’arudl Al-Adillah - Bawon, Jumrotul; Nabilah, Fa’izah Dwi; Yunus, Jefrizal (Maliki Interdisciplinary Journal, 2024)
This article explains the concept of "Ta'arudl al-Adillah and Tarjih" in the discussion of ushul fiqh. Ta'arudl al-Adillah refers to the contradiction between legal propositions, while Tarjih is more directed at finding the strongest proposition between two contradictory propositions. So, this article aims to find a solution that occurs in conflicting propositions. The method used in this research is to use library research by collecting relevant data from books, dictionaries, journals, magazines, and so on without having to do research in the field. So the results of this study are known Ta'arudl al-Adillah has causes, conditions, types and methods of settlement. In the process of resolving contradictions in the arguments there are several causes, conditions, and steps in it. And it has also been found that Tarjih is also one of several methods in resolving conflicts in these arguments. Thus it can be concluded that Ta'arudl al-Adillah and Tarjih are very sustainable between two contradictory propositions and how to resolve them.